Penerapan Fuzzy String Matching Pada Aplikasi Pencarian Judul Skripsi Teknik Informatika Berbasis Android - Khairunnisa Khairunnisa (JURIKOM (Jurnal Riset Komputer), 2019)
The library is the center of the gathering of various information and knowledge both in the form of books and other recording materials to meet the needs of the learning process. In addition to storing books, the library also stores final assignment documents or thesis of students who have graduated from the college. This description can usually be used as a reference material for students in preparing the final assignment. The more years the number of thesis increases so that it requires a storage space the wider. The problem that is often faced by students is that the thesis search process needed as reference material takes a long time. From these problems it is necessary to make innovations by utilizing information technology. Mobile phones are not only used to call and send messages, but cellphones also have various other functions such as internet access, audio and video player media, and so on. Android is one of the operating systems for mobile phones among the development of other mobile operating systems such as Windows Mobile, Symbian, Blackberry OS and others. In this study, we will build a repository application for an Android-based thesis search that is built by applying the Fuzzy String Matching algorithm. Fuzzy String Matching Algorithm is one of the string search methods that uses the approach process to the pattern of the string being searched for. Search for the same string and also the string that approaches the other strings collected in a container or dictionary. By utilizing the Fuzzy String Matching algorithm in the thesis search application on informatics engineering, it is expected to be able to search quickly and efficiently.